Efektivitas Outbound Management Training Terhadap Stres Kerja Pada Pegawai Bank Swasta di Surakarta - Setyarini, Nita Dwi, Dr. Wiwien Dinar Pratisti, M.Si, Psi (2017)
More stringent competition in the banking sector with a number of competitors current-carrying competition would not only in price competition and flowers , but also in non-price competition.Competition in quality it will lead to on good corporate governance ( GCG ) .In the midst of this , banking industry are required to can increase their competitiveness.The state of the total are developing regulations to organization and standard operating high for reached goals desired company. But in fact regulations , the physical condition , climate , culture work , demand and the target company such high to cause the presence of working stress on employees. Working stress on employees also can be reduced by to play.Play here is the shape of the activity of outbond management training or OMT. Methodology of OMT is the formation of experience , experience however this is not obtained from daily activity but from the fun game and excitinggame that is given in the omt .The purpose of this study is to determine effect of outbound management training in reducing stress on employees bank.The subject of this research as many as 42 people elected purposively the sampling method of which a subject is divided into groups experimentation and the control group with characteristics employee of a bank bri with stress level moderate to high.A method of this research uses experimental methods pretest posttest control group design .The result of this research analyz-ed using gain-score then tested with independent sample test obtained value t = -9,790 with standard siginifikansi ( p ) = 0,000 means that there is a difference of employees of the bank levels before and after outbound management training (OMT), wherethe stress levels of employees of the bank is decreased employee after joining outbound management training (OMT). This means that outbound management training (OMT) can reduce stress levels of employees.